Nanocomposites for bone tissue regeneration. (April 2013) - Sahoo, Nanda Gopal; Pan, Yong Zheng; Li, Lin; He, Chao Bin
Natural bone tissue possesses a nanocomposite structure that provides appropriate physical and biological properties. For bone tissue regeneration, it is crucial for the biomaterial to mimic living bone tissue. Since no single type of material is able to mimic the composition, structure and properties of native bone, nanocomposites are the best choice for bone tissue regeneration as they can provide the appropriate matrix environment, integrate desirable biological properties, and provide controlled, sequential delivery of multiple growth factors for the different stages of bone tissue regeneration. This article reviews the composition, structure and properties of advanced nanocomposites for bone tissue regeneration. It covers aspects of interest such as the biomimetic synthesis of bone-like nanocomposites, guided bone regeneration from inert biomaterials and bioactive nanocomposites, and nanocomposite scaffolds for bone tissue regeneration. The design, fabrication, and in vitro and in vivo characterization of such nanocomposites are reviewed.